Overall Characteristics of Nationwide High PM2.5 Episodes during 2013~2016 2013~2016 기간 전국 규모 PM2.5 고농도 사례의 전반적 특성 - Ghim, Young Sung; Choi, Yongjoo; Park, Jisoo; Kim, Soontae; Bae, Chang Han; Seo, Jihoon; Shin, Hye Jung; Lim, Yong Jae; Lyu, Young Sook; Lee, Young Jae (Journal of Korean Society for Atmospheric Environment, 2019)
Five nationwide high PM2.5 episodes were selected using data from intensive air quality monitoring stations operated by the National Institute of Environmental Research during 2013~2016. Episode selection was based on the number of stations with mean PM2.5≥75 μg/m3, number of episode days, and mean PM2.5, considering season. PM2.5 concentration increased mainly with sulfate as air trajectories arrived from polluted regions in China, when the Chinese contribution was high. Although not as prominent as sulfate, high nitrate concentration in the case of high PM2.5, and K+ enrichment in the case of high Chinese contribution were observed during some episodes. While sulfate and nitrate behaved similarly in many cases, the difference in concentration between sulfate and nitrate was useful in determining the relative importance of long-range transport and local emissions. Long-range transport of pollutants from China, which played a vital role in leading to high PM2.5, was primarily associated with development and movement of migratory high-pressure system. As a high-pressure system developed, pollutants accumulated in the northern part of China and were transported to the Korean Peninsula along with the eastward movement of the high-pressure system. High PM2.5 concentrations occurred while the high-pressure system resided over the Korean Peninsula and the domestic contribution increased
Keywords: Chinese contribution; Episode selection; Nitrate; Sulfate; Synoptic meteorology